Comprehensive Review of Skiing and Snowboarding Injuries. Issue 1 (1st January 2018) - Owens, Brett D.; Nacca, Christopher; Harris, Andrew P.; Feller, Ross J.
Abstract : Skiing and snowboarding have increased in popularity since the 1960s. Both sports are responsible for a substantial number of musculoskeletal injuries treated annually by orthopaedic surgeons. Specific injury patterns and mechanisms associated with skiing and snowboarding have been identified. No anatomic location is exempt from injury, including the head, spine, pelvis, and upper and lower extremities. In these sports, characteristic injury mechanisms often are related to the position of the limbs during injury, the athlete's expertise level, and equipment design. Controversy exists about the effectiveness of knee bracing and wrist guards in reducing the incidence of these injuries. Understanding these injury patterns, proper training, and the use of injury prevention measures, such as protective equipment, may reduce the overall incidence of these potentially debilitating injuries.